Food security, nutrition and health nexus on undernutrition reduction in Indonesia: Enabling resilience system into emergency preparedness - Rusyda, Akifa Laila (Journal of Community Empowerment for Health, 2025)
Introduction: Evidence on the integration of nutrition interventions into existing health system program needs to be further explored. The study examined influence of food security, essential nutritional intervention, and health coverage towards undernutrition reduction in Indonesia during the emergency situation (in the context of COVID-19 pandemic). In addition, the study identified also the collaborative role in reducing undernutrition followed by the existing theoretical concepts.Methods: The design of the study was ecological study using secondary data from Indonesian Health Profile, Food Security Statistics, and National Socio-economic Survey between 2020 and 2021. The total unit of analysis was 68, representing all provinces in Indonesia with resampling bootstrapping approach. The analysis was conducted using partial-least square structural equation modeling (PLS-SEM).Results: Reduction of undernutrition status was statistically driven by essential nutrition intervention (t =1.981; p=0.048) and food security (t =2.377; p=0.018). Finding also shows that food security was influenced by food accessibility (t =2.867; p=0.004) and food consumption (t=4.800; p=0.000). Furthermore, the health service coverage significantly influenced essential nutrition intervention (t=5.350; p=0.000) and health service coverage must be supported by health financing coverage (t=6.042; p=0.000).Conclusion: Integrating food security, essential nutrition intervention, and health coverage may strongly build a resilience system during a pandemic based on predictive relevance (Q2=94%). These three components can also be applied during emergency preparedness.